FPGA Based Fault Tolerant Scheme on Four Switch Voltage Source Inverter - M., Ayyakrishnan (Institute of Advanced Engineering and Science, 2015)
This paper presents an efficient methodology to detect the fault occurrence and its tolerance of four switch voltage source inverter in a single Xilinx Spartan 3E Field Pro-grammable Gate Array (FPGA). The merit of this proposed system reduces the time period between fault existence and its isolation with four switches in two legs instead of six switches in three legs so as to minimize the switching losses, accuracy, and better recovery time. The FPGA platform supports the run-time reconfiguration of control functions and algorithms directly in hardware and meets hard real-time performance criteria in terms of timings for SVPWM generation, fault detection time and fault tolerance time. Simulation and Experimental results of this proposed system is demonstrated and verified.